Is translation indispensable? Several remarks on the Latin language in the world of Roman law studies in Poland - Kulawiak-Cyrankowska, Joanna (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The decline of Latin in Polish schools starts to affect the Academia as well. The author of this paper draws attention to the trend of translating the Roman legal sources in the body of papers published by Polish Romanist lawyers. This increasingly common practice seems to be indispensable if the authors want their readers, however belonging to the narrow group of Romanists, to follow their writing. On the one hand, Latin language skills are an essential part of research competences of a Romanist lawyer. On the other hand, however, there rises a risk that the researchers of Roman law soon will not be able to translate the legal sources on their own, which calls into question the quality of the study of Roman law in the near future.